Maternal western-style diet alters Kupffer cell proportion leading to metabolic dysfunction-associated steatotic liver disease when challenged with western diet in adulthood - Miller, Sarah J.; Janssen, Rachel C.; Zhao, Wanke; Jonscher, Karen R.; Zhong, Hua; DeVette, Christa I.; Friedman, Jacob E.; Zimmerman, Kurt A. (Frontiers in Immunology, 2025)
Exposure to maternal western-style diet (mWD) is associated with early development of metabolic dysfunction-associated fatty liver disease (MAFLD) in offspring. Kupffer cells (KCs), the main resident macrophage population in the liver, are known to promote MAFLD progression; however, the effects of mWD on KC subtypes, ontogeny, and gene expression in offspring are not fully understood. In this manuscript, we used two different models of mWD exposure and challenge in adulthood to understand the impact of mWD on KC proportion, ontogeny, and gene expression in adult offspring. Our data indicate that in the absence of challenge in adulthood, mWD results in increased KC proportion in offspring, with limited changes in KC ontogeny or liver phenotype. In contrast, mWD mice challenged with WD in adulthood had increased expression of inflammatory (Nlrp3) and fibrosis (Tgfb1)-related genes compared with chow (CH)-WD-fed mice. Although KC proportion and ontogeny were similar when comparing CH-WD- and WD-WD-fed mice, we found that WD-WD mice had a greater reduction in KC proportion and TdT labeling than CH-WD-fed mice when normalized to their respective maternal diet controls. Similar results were found when mice were weaned onto normal chow and rechallenged with WD later on in adulthood. Bulk RNA sequencing data indicate that KCs from mWD mice rechallenged with WD in adulthood had increased expression of inflammatory and antigen-presenting genes compared with KCs isolated from WD-fed mice lacking mWD exposure. These findings highlight the intergenerational repercussions of mWD on liver phenotype as well as KC proportion and ontogeny and provide novel insight into the mechanisms dictating MAFLD.